2018
DOI: 10.7150/ntno.28046
|View full text |Cite
|
Sign up to set email alerts
|

MnO2-gated Nanoplatforms with Targeted Controlled Drug Release and Contrast-Enhanced MRI Properties: from 2D Cell Culture to 3D Biomimetic Hydrogels

Abstract: Multifunctional nanomaterials combining diagnosis and therapeutic properties have attracted a considerable attention in cancer research. Yet some important challenges are still to be faced, including an optimal coupling between these two types of properties that would be effective within complex biological tissues. To address these points, we have prepared novel nanoplatforms associating controlled drug delivery of doxorubicin and Magnetic Resonance Imaging (MRI) contrast-enhancement that exhibit high specific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…As an alternative, manganese oxide (MnO) NPs provide the advantage over iron oxide in that they can provide switchable, bright contrast on T 1 MRI due to the paramagnetic properties of the Mn 2+ ion. Our group and other studies have shown that intact MnO NPs are in an “OFF” state and create minimal T 1 MRI signal due to the Mn 2+ ions being tightly bound and inaccessible to the surrounding water molecules [ 5 10 ]. In acidic media, MnO dissolves to form Mn 2+ , which coordinates with water molecules to decrease T 1 and produce a positive MRI signal, thus turning “ON” MRI contrast [ 5 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, manganese oxide (MnO) NPs provide the advantage over iron oxide in that they can provide switchable, bright contrast on T 1 MRI due to the paramagnetic properties of the Mn 2+ ion. Our group and other studies have shown that intact MnO NPs are in an “OFF” state and create minimal T 1 MRI signal due to the Mn 2+ ions being tightly bound and inaccessible to the surrounding water molecules [ 5 10 ]. In acidic media, MnO dissolves to form Mn 2+ , which coordinates with water molecules to decrease T 1 and produce a positive MRI signal, thus turning “ON” MRI contrast [ 5 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The larger the pores, the larger the size of protein molecules that can pass through, and the faster the material metabolism. [ 169 ] A hydrogel itself can also be loaded with drugs, [ 170,171 ] biological factors, [ 172,173 ] and other substances [ 174 ] during the cultivation process, and they are slowly released into the cultivation system. During the synthesis of hydrogel materials, chemical bonds or covalent bonds are used to access drug groups or protein groups, which can better control the release of drugs.…”
Section: Difficulties and Challenges We Faced In Switching Over From 2d Cell Culture To 3d Cell Culturementioning
confidence: 99%
“…Cells from the bioreactor were transferred to tubes to increase their concentration in a small volume. There are many studies in the literature that discuss measuring the relaxation time of cell cultures [6][7][8][9][10]. To determine the T 1 time, the study was carried out in the T 1 FSE sequence.…”
Section: Cell Culture Measurementsmentioning
confidence: 99%
“…If we assume that for calculations we will always take the same area in the image, and the result of the test will shift the examined structures, and the ROI will accidentally find adjacent tissues not covered by measurement in other sequences, this may lead to falsification of the IS value and thus increase the uncertainty of the relaxation time measurement result. Analysing the work of various authors, many solutions can be found to increase the speed of obtaining the T 1 times [7][8][9][11][12][13][14]. The vast majority of them, however, essentially use SR or IR methods.…”
Section: Equationmentioning
confidence: 99%